Burning Mouth Syndrome Treatment. A challenge to Evidence-Based Medicine - Rook de Lima, Guilherme; Faustino, Sara (Family Medicine & Primary Care Review, 2022)
Burning Mouth Syndrome (BMS) is defined as a burning sensation or numbness in the oral mucosa, which occurs more than 2 hours per day for more than 3 months, in the absence of clinical changes. The prevalence varies between 0.1 and 7%. Of unknown aetiology, it is more frequent in individuals with anxiety, personality disorders and depression, affecting quality of life (QoL). The objective of this article is to review the effectiveness of existing therapies versus a placebo regarding symptomatic relief and changes in QoL. Research was carried out during December 2020 utilising PubMed and The Cochrane Library databases, with the MeSH terms “burning mouth syndrome treatment”. This research was limited to randomised clinical trials including a placebo group, published after a systematic review by Cochrane in 2016, in English. To classify levels of evidence and the strength of recommendations, we used the “Strength of Recommendation Taxonomy of the American Academy of Family Physicians”. In studies with a low level of evidence, there seems to be symptomatic improvement with laser radiation, palmitoylethanolamide tablets and serotonin reuptake inhibitors. Oral melatonin and topical chamomile therapy are no better than a placebo. This is a difficult condition to treat, in which there is limited evidence. Fluoxetine seems to play a role in the long-term symptomatic improvement of these patients, and low-level laser therapy is an alternative therapy to consider. As it is a condition of unknown aetiology, and it is difficult to find adequate treatment with consistent results.